Determinant of Medication Administration Error Occurrence From Nurse Aspect At Haji Hospital Makassar - Achmad Indra Awaluddin; A.Indahwaty Sidin; Anwar Mallongi (International Journal of Nursing and Health Services (IJNHS), 2021)
Introduction: The nurse organizes almost all the medication in the hospital. Objective: This study aimed to determine the influence of medication error (administration error) events from nurses at Haji Hospital Makassar in 2017. Method: This research was a quantitative research type. The design used was analytic observational with a cross-sectional approach. The purposive sampling technique determines a sample of 101 people. Data were analyzed quantitatively by using statistic analysis of cross-tabulation, chi-square, and then logistic regression analysis. Result: The results showed that the prevalence of medication error (administration error) was 166 incidents. Variables of a heavy workload, Personal Neglect, Unfamiliarity with medication, and New Staff influenced medication error (administration error). In contrast, the Complicated Doctor-initiated order, Complicated Order, and Insufficient training variables did not affect the medication error (administration error). And the most significant variable is heavy workload with p value=0.027<0.05 and OR value=0.106. Recommendation: It is expected to further research to explore more variables related to medication administration Error at the hospital